Penggunaan Media Audio Visual Dalam Pembelajaran Seni Tari Untuk Meningkatkan Hasil Belajar Siswa di Kelas XI IPA 3 SMAN 1 Ulakan Tapakis Kabupaten Padang Pariaman - Siti Nur Azizah; Susmiarti Susmiarti (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to delineate and elucidate the manner in which audiovisual media may be employed to enhance the academic achievements of students enrolled in dance in XI IPA 3 SMAN 1 Ulakan Tapakis. Classroom action research was the twice-repeated method of inquiry. Thirty students enrolled in class XI IPA 3 at SMAN I Ulakan Tapakis participated in the investigation. The data were acquired by consulting relevant documentation, observation logs, cognitive knowledge test outcomes, and psychomotor skills test results. The results of this study indicate that the integration of audiovisual resources into the dance curriculum at SMAN 1 Ulakan Tapakis's class XI IPA 3 had a substantial beneficial effect on the academic achievement of the students. This is supported by the substantial improvement in pupil learning outcomes during cycles I and II. In its totality, Cycle I exhibited a learner activity rate of 40%. In contrast, during the entire duration of the second cycle, student engagement increased by 83%. Cycle I yielded an overall pupil learning outcome of 63%. On the contrary, cumulative student learning outcomes exhibited a surge to 90% in cycle II. Therefore, the effective implementation of incorporating audiovisual materials into SMAN I Ulakan Tapakis, which is part of the XI IPA 3 course, has enhanced the results of dance education.